Study of Maternal Near Miss in Tertiary Care Center: Prospective Observational Study in Lady Hardinge Medical College, Delhi, India - Prasad, Chandrakanta; Gupta, Bhavna; Singh, Abha (International Journal of Innovative Research in Medical Science, 2022)
To study the causes responsible for maternal near miss morbidity and mortality. To evaluate the avoidable factors in maternal near miss morbidity and maternal mortality. A sample size of 100 pregnant woman who satisfy the WHO inclusion criteria for MNM and all maternal mortality during the study period. A detailed history obstetric examination, informed consent, demographic profile like age, parity, booking status, gestational age, h/o obstetric complications were taken, presence of organ dysfunction, ICU admission, the hospital course, delays at the level of the patient and reasons for referral to this Hospital were taken followed till delivery and maternal outcome observed. In a period of one year, there were 2,085 deliveries,1578 live births,507 still birth, Mean age of near miss was 26.30±4.70 year (41.98%) and average maternal death was 25.89. WLTC-100. MNM was 81 cases. Maternal death was 19 cases. Maternal near miss ratio was 51.33/1000 live birth .Maternal near miss mortality ratio is4.3:1(MNM/MD)-Mortality Index was 19%. SMOR 63.53/1000 LB. MMR=101.57/100,000 LB. According to the result and discussion it is concluded that haemorrhage and hypertension were the leading cause of near miss events. As near miss analysis indicates the quality of health care and a good alternative indicator of health care system.